2007
DOI: 10.1097/fjc.0b013e318046f34a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of p38 MAPK Inhibitor on Angiotensin II-Dependent Hypertension, Organ Damage, and Superoxide Anion Production

Abstract: Angiotensin II (Ang II) activates p38 mitogen-activated protein kinase (p38 MAPK) and increases reactive oxygen species (ROS), but the nature of the relationship in vivo is not fully understood. We assess the effect of SB239063AN, a highly selective, orally active, p38 MAPK inhibitor, on Ang II-dependent hypertension, target-organ damage and ROS production. Sprague-Dawley rats and MAPKAP kinase-2 knockout mice were infused with Ang II. Ang II infusion increased the levels of phosphorylated p38 MAPK in the hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 25 publications
6
71
0
Order By: Relevance
“…Several studies showed that in vivo chronic inhibition of p38-MAPK downregulates NADPH oxidase expression, attenuates superoxide production, and improves vascular function in a variety of animal models (8,46,49). Also, it has been reported that acute inhibition of p38-MAPK suppresses NADPH oxidase in neutrophils (26).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that in vivo chronic inhibition of p38-MAPK downregulates NADPH oxidase expression, attenuates superoxide production, and improves vascular function in a variety of animal models (8,46,49). Also, it has been reported that acute inhibition of p38-MAPK suppresses NADPH oxidase in neutrophils (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, EGCG was effective in reducing CoCl2-derived ROS [33]. Ang II activated p38 MAPK and increased ROS in the vasculature [34]. Therefore, an inhibition of NADPH oxidase expression by EGCG may be insufficient to affect ROS production in HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al 34) described that treatments with p38 MAPK inhibitor suppressed myocardial fibrosis and LV remodeling, and attenuated the expressions of p-p38-MAPK, TNF-, -SMA and type collagen as compared with rats with myocardial ischemia. Bao et al 15) indicated that Ang -induced hypertension, organ damage, and ROS production are possibly mediated by p38 MAPK and inhibition of p38 MAPK may offer a therapeutic approach for cardiovascular disease. In addition, their group also investigated that chronic treatment with p38 MAPK inhibitor significantly reduces target-organ damage in salt-sensitive stroke-prone spontaneous hypertensive rats, and is associated with the preservation of endothelial function 5)…”
Section: Discussionmentioning
confidence: 99%
“…Upon stimulation, the cytosolic complex migrates and assembles with the membrane subunits to form an active oxidase capable of producing superoxide anion 13) , and NAD(P)H oxidase plays a critical role in intracellular redox signaling and has been implicated in various cardiovascular diseases 14) . Specifically, the interaction of superoxide anion with nitric oxide reduces nitric oxide bioavailability and produces toxic peroxynitrite, resulting in endothelial dysfunction, which is a hallmark of hypertension, heart failure, and atherosclerosis 15) . Recent studies demonstrated that p38 MAPK activates NAD(P)H oxidase by enhancing the phosphorylation and assembly of NAD(P)H oxidase subunits, and the activation of NAD(P)H oxidase is suppressed by p38 MAPK inhibitors 16) .…”
Section: Introductionmentioning
confidence: 99%